MITOS DAN NILAI AJARAN ISLAM DALAM TRADISI APITAN SEBAGAI BUDAYA JAWA DI DESA MEDANI KECAMATAN TEGOWANU KABUPATEN GROBOGAN - Dewi Mudrikah; Serli Wulandari; Indah Zulaikha (Batuthah)
This article examines the myth of shadow puppet performances in the Apitan tradition in Medani Village, Tegowanu District, Grobogan Regency. The aim of this study is to find out the mythical narrative of wayang kulit performances in the Apitan tradition in Medani Village. This research uses historical methods with data collection techniques in the form of interviews and literature studies. The results of the research show that, in the myth of the shadow puppet show, there are two mythical narrative stories, namely the first version, which was long believed by native Medani residents with the belief that it is a myth, the first appeared when they once did not perform the Apitan wayang dhanyang, an angry pagebluk occurred and the second version was only believed by newcomers with mythical beliefs. This arose as a result of the spread of disease outbreaks due to the lack of knowledge among residents regarding hygiene and disease management, resulting in a disaster where many residents died simultaneously. The symbolic function of the Apitan tradition for Medani residents is intended to provide reinforcements to obtain safety for Medani residents from the influence of bad things or spiritual threats. Apart from that, it also increases the self-confidence felt by each Medani resident. And strengthening harmony between Medani residents is the result of a series of developing Apitan traditional events.